Design Architecture Smart Heatsink Laptop untuk Mengatasi Overheat dan Korslet Motherboard - el fazza, fahri (Jurnal Ilmiah Sistem Informasi dan Teknik Informatika (JISTI), 2024)
Technological developments, especially in the field of computer architecture, are growing very rapidly. The role of cooling is a major factor in reducing the risk of damage that generally occurs, such as overheating and short circuits. Overheating on a laptop can cause the laptop to shut down and slow performance. The cause of overheating is due to air blockages in the heatsink fins so that hot air from the processor cannot escape from the laptop. Heatsink fins that are still static provide access for dust to enter and exit, causing blockages. Dynamic Smart Heatsink architecture can open and close automatically so that the laptop can be protected from external interference such as dust and animals.